1998
DOI: 10.1016/s0735-1097(98)00205-8
|View full text |Cite
|
Sign up to set email alerts
|

T wave normalization in infarct-related electrocardiographic leads during exercise testing for detection of residual viability

Abstract: Exercise-induced TWN on IRLs at low work loads is a sensitive and specific index for the presence of residual viability in the infarct area. Sensitivity and diagnostic accuracy of this sign are higher for anterior infarctions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
2

Year Published

2000
2000
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 24 publications
0
8
0
2
Order By: Relevance
“…Several methods have been successfully used to detect viable myocardium and persistent myocardial ischemia in the peri-infarction zone including angiographic, scintigraphic and echocardiographic techniques. Recently, it has been shown that exercise-induced ST segment elevation and T wave normalization predict viable myocardium in the infarct region with good accuracy [4, 5, 6, 7, 8]. Scintigraphic and echocardiographic techniques are widely used to detect myocardial viability and ischemia, and have become standard techniques for the evaluation of viability and ischemia in patients with wall motion abnormalities after MI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several methods have been successfully used to detect viable myocardium and persistent myocardial ischemia in the peri-infarction zone including angiographic, scintigraphic and echocardiographic techniques. Recently, it has been shown that exercise-induced ST segment elevation and T wave normalization predict viable myocardium in the infarct region with good accuracy [4, 5, 6, 7, 8]. Scintigraphic and echocardiographic techniques are widely used to detect myocardial viability and ischemia, and have become standard techniques for the evaluation of viability and ischemia in patients with wall motion abnormalities after MI.…”
Section: Discussionmentioning
confidence: 99%
“…Normalization of negative T waves (TWN) on IRLs during exercise tests or dobutamine stress tests in patients with previous MI has recently been shown to represent the presence of ischemic but viable myocardium within the infarct area [4, 5, 6, 7, 8]. Identification of residual viability of areas of the myocardium that could be saved by a revascularization procedure is very important information for the cardiologist.…”
Section: Introductionmentioning
confidence: 99%
“…In the GISSI-3 (third Gruppo Italiano per lo Studio della Sopravvivenza nell'Infarto Miocardico) echo substudy, the number of negative T waves decreased at six months in the majority of patients and this was associated with substantial recovery of regional dysfunction. 9 T wave normalisation induced by exercise testing predicts myocardial viability 8 and is often associated with late spontaneous T wave normalisation on the resting ECG. 13 In the chronic phase of infarction, patients with restored positive T waves who benefited from optimal revascularisation of the infarct related artery have better contractile reserve, shown with low dose dobutamine stress echocardiography, than those with negative T waves.…”
Section: T Wave Evolution and Left Ventricular Functionmentioning
confidence: 99%
“…Various ECG parameters at rest or during exercise were applied to assess myocardial viability or recovery of functionfor example, QT dispersion and T-wave normalization 9,10 -in a population with severely diseased but mostly patent arteries. The extent of Q waves in the resting ECG was used to assess a QRS score (Selvester Score) to predict infarct size and LV function after myocardial infarction (MI).…”
Section: Introductionmentioning
confidence: 99%